The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1029/jc088ic06p03741
|View full text |Cite
|
Sign up to set email alerts
|

A decade of stratospheric sulfate measurements compared with observations of volcanic eruptions

Abstract: Sulfate aerosol concentrations in the stratosphere have been measured for 11 years (1971–1981) using portions of filters collected by the Department of Energy's High Altitude Sampling Program. Data collected seasonally at altitudes between 13 km and 20 km spanning latitudes from 75°N to 51°S are reported. These data are compared with the reported altitudes of volcanic eruption plumes during the same decade. From this comparison it is concluded that (1) several unreported volcanic eruptions or eruptions to alti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 36 publications
3
37
0
Order By: Relevance
“…The 20 July 1978 eruption is not listed by Simkin et al (1981) and Sedlacek et al (1983) concluded that either the documen tation for the Dukono eruption is incomplete or another volcano has injected material but not been observed.…”
Section: Methodsmentioning
confidence: 85%
See 3 more Smart Citations
“…The 20 July 1978 eruption is not listed by Simkin et al (1981) and Sedlacek et al (1983) concluded that either the documen tation for the Dukono eruption is incomplete or another volcano has injected material but not been observed.…”
Section: Methodsmentioning
confidence: 85%
“…Livingston et al (1983) have reported the existence of a 'mistery' cloud over Japan and in the western United States shortly before the 28 March 1982 eruption of El Chi chon. Sedlacek et al (1983) reported on the oc currence of greatly elevated sulfate concentra tions at three altitudes (about 15, 17 and 19km) between 10°N and 20°N in samples collected on July 24 and July 25, 1978 (see a peak sulfate concentration which occurred in the middle of 1978 in Fig. 2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The flow of sulphur into the stratosphere is dominated by large explosive eruptions which account for about 60% of stratospheric sulphur E. J. HIGHWOOD budget (Sedlacek et al 1983). Pyle et al (1996) estimate that on average about 0.06-0.15 Mt/y of stratospheric sulphur (as SO2) is from nonvolcanic sources, while about 1 Mt/y arises from volcanic injection.…”
Section: Development Of the Aerosol Cloudmentioning
confidence: 99%